Anti-aquaporin-4 immunoglobulin G colorimetric detection by silver nanoparticles - Higa, Akemi M.; Moraes, Ariana S.; Shimizu, Flávio M.; Bueno, Raquel G.; Peroni, Luís A.; Strixino, Francisco T.; Sousa, Nise A.C.; Deffune, Elenice [UNESP]; Bovolato, Ana Lívia C. [UNESP]; Oliveira, Osvaldo N.; Brum, Doralina G. [UNESP]; Leite, Fabio L. (Elsevier, 2022)
Neuromyelitis optica spectrum disorder (NMOSD) is an inflammatory and autoimmune disease whose biomarker is the anti-AQP4-IgG autoantibody that binds to aquaporin-4 (AQP4) protein. We introduced a nanosensor with a sensitivity of 84.6%, higher than the CBA's 76.5%. Using silver nanoparticles (AgNPs), we detected not only seropositive but also some false-negative patients previously classified with CBA. It consisted of AgNPs coated with one of a panel of 5 AQP4 epitopes. The ability in detecting the anti-AQP4-IgG in NMOSD patients depended on the epitope and synergy could be obtained by combining different epitopes. We demonstrated that NMOSD patients could easily be distinguished from healthy subjects and patients with multiple sclerosis. Using the most sensitive AQP461-70 peptide, we established a calibration curve to estimate the concentration of anti-AQP4-IgG in seropositive NMOSD patients. The ability to enhance the accuracy of the diagnosis may improve the prognosis of 10-27% of anti-AQP4-IgG seronegative patients worldwide.
Keywords: Anti-aquaporin-4 immunoglobulin G; Diagnosis; Epitopes; Neuromyelitis optica spectrum disorders; Silver nanoparticles